Proton Transfer‐Driven Modification of 3D Hybrid Perovskites to Form Oriented 2D Ruddlesden–Popper Phases. Issue 3 (23rd December 2021) - Duan, Zonghui; Na, Guangren; Wang, Shixun; Ning, Jiajia; Xing, Bangyu; Huang, Fei; Portniagin, Arsenii S.; Kershaw, Stephen V.; Zhang, Lijun; Rogach, Andrey L.
Abstract : Herein, it is shown how a proton transfer process between the organic moiety in 3D methylammonium lead halide perovskite and the introduced aliphatic alkylamines provides the basis for a fabrication route toward hybrid 3D/2D perovskites and finally purely 2D Ruddlesden–Popper (RP) perovskite phases, predominantly the n = 1 phase. Five alkylamines with varying aliphatic chain lengths, such as butylamine, octylamine, dodecylamine, hexadecylamine, and octadecylamine as antisolvents in toluene, are used, which quickly protonate during the spin‐coating deposition of thin perovskite films. Formation of hydrogen bonds between protonated alkylamines and lead halide slabs leads to mixed 3D/2D hybrid perovskites, where the ratio between the 3D and 2D phases can be adjusted by the concentration of the alkylamine containing antisolvents. Longer‐chain aliphatic alkylamines (12 carbon atoms or greater) are most prone to slice 3D perovskite into layered perovskites with efficient green emission reaching up to 38% for their photoluminescence quantum yield in films. Above a certain concentration threshold, 3D perovskite can be completely modified into 2D RP perovskite phases with crystalline orientation parallel to the substrate. The introduced facile perovskite phase modification approach provides a convenient way toward different kinds of 2D RP metal halide perovskite films with attractive optical properties. Abstract : A proton transfer process between the methylammonium cations in the 3D lead halide perovskite framework and the introduced alkylamine additives with varying aliphatic chain lengths results in the formation of composite 3D/2D hybrid perovskites with efficient green emission, and finally purely 2D Ruddlesden–Popper (RP) perovskite films with attractive optical properties.